DIFFERENCES IN THE DEHYDRATION-REHYDRATION BEHAVIOR OF HALLOYSITES: NEW EVIDENCE AND INTERPRETATIONS - Joussein E.; Petit S.; Fialips C.; Vieillard Ph.; Righi D. (My University, 2006)
Two reference halloysites from New Zealand (Te Puke and Opotiki) were studied by X-ray diffraction under (1) various levels of relative humidity (RH) from 95 to 0% (dehydration), and (2) various temperatures increasing from 25 to 120°C (dehydration). They were also studied by differential thermal and thermogravimetric analyses at 40 and 0.2% RH. The impact of freeze drying along with the influence of cation saturation (Ca and K) on halloysite hydration were studied. The dehydration of the two halloysite samples upon decrease in RH started below 70% RH. However, the dehydration of Opotiki was still incomplete at ~0% RH regardless of the saturation cation whereas Te Puke was completely dehydrated at ~10% RH. For each sample, the decrease in RH and the increase in temperature induce similar dehydration behavior, but the dehydration processes of the Opotiki and Te Puke samples are different. The dehydration of Te Puke proceeds with one intermediate hydration state reacting as a separate phase due to the presence of ‘hole’ water molecules. The dehydration of the fully hydrated Opotiki halloysite gives a dehydrated phase and no 8.6 Å phase. The results suggest the presence of different types of water molecule, the ‘associated’ and the ‘hole’ water, controlling the dehydration behavior of halloysites. Freeze-dried halloysite samples are essentially dehydrated and the size of their coherent scattering domains is strongly reduced. Rehydration experiments performed after dehydration either at 95% RH or by immersing the sample in water for 3 months result in their partial rehydration. Calcium saturation promotes the rehydration process. The results suggest the presence of interlayer cations in the Opotiki sample, Ca ions being associated with the strongly held ‘hole’ water. As a result of this study, we assert that the (de)hydration behavior of halloysite is highly heterogeneous and cannot be generalized a priori.
Keywords: DEHYDRATION; DTA-TGA; FREEZE DRYING; HALLOYSITE; HEATING; HYDRATION; RELATIVE HUMIDITY; SATURATING CATIONS; WATER STATUS; XRD